Photocatalytic Activity of Nanosized Cadmium Sulfides Synthesized by Complex Compound Thermolysis. (18th August 2010) - Yu, Yingchun; Ding, Youxian; Zuo, Shengli; Liu, Jianjun
Abstract : The nanosized cadmium sulfides (CdSs) containing different phase structures were synthesized via the complex compound thermolysis method using different molar ratio of thiourea to acetate cadmium (S/Cd) and characterized by XRD, TEM, UV-Vis, and IR spectra. The results of photocatalytic degradation of rhodamine B (RB) show that the activity order of CdS concerning the phase compositions is of cubic> hexagonal> cubic + hexagonal, where the CdS with the cubic phase has the best photocatalytic degradation activity of RB due to its larger abilities of adsorption and absorbance and smaller particle size of about 10 13 nm.